Child sexual abuse - Tenorio Castro, Milena (2003)
This article focuses Child sexual abuse as part of Child Abuse. The situations in which sexual abuse occur and the factors which increase the sexual abuse impact are also examined. The sexuality abuse child´s profile is described and the way to cope the problem is also analyzed.